Meteorin-like protein may be a mediator of exercise-related reproductive disorders in female rats - Ulker Ertugrul, Nazife; Keskin Buyukbudak, Feyza; Delice, Nurcan; Gokdere, Ebru; Dogru, Meryem Sedef; Ertugrul, Tugrul; Canpolat, Sinan (Nature Portfolio, 2026)
Exercise provides significant benefits for most women, but adverse effects on reproduction can and do occur. Increased frequency, duration, and intensity of exercise are associated with a higher risk of female infertility. In particular, exercise-induced reproductive dysfunction is linked to alterations in the hypothalamic-pituitary-gonadal (HPG) axis. However, the role of meteorin-like protein (metrnl), as an exercise-induced myokine, in female reproductive function and the HPG axis is not yet fully understood. In this study, we investigated the effects of metrnl, compared with a swimming exercise protocol, on sexual motivation and the HPG axis in female rats. Female rats with regular estrous cycles were randomly allocated into three groups (n = 9 per group), and subjected to deionized water (1 mL/kg), metrnl (1 & micro;g/day) or swimming-based moderate-intensity exercise (30 min/day, 5 days/week) for about 19 consecutive days. The results showed that metrnl administration reduced the time spent near the male rat and the male preference ratio, indicators of sexual motivation. It also decreased hypothalamic GnRH expression (in the median eminence and preoptic area), serum concentrations of reproductive hormones (follicle-stimulating hormone and anti-M & uuml;llerian hormone), and the numbers of ovarian follicles (primordial and primary follicles), similar to the effects observed after the swimming exercise protocol. Furthermore, metrnl concentrations in serum remained unchanged in female rats treated with metrnl and exercise. In conclusion, metrnl treatment reduced sexual incentive motivation and altered HPG axis regulation in female rats. These findings suggest that exercise-induced metrnl may be a potential exerkine associated with changes in female sexual motivation and HPG axis regulation due to exercise.
Keywords: Meteorin-Like Protein (Metrnl); Moderate-Intensity Exercise; Reproduction; Sexual Incentive Motivation; Hpg Axis; Gnrh